(untitled) (Praxis Educativa, 2012)
This article presents the results of part of a research project that examined the degree of articulation between students thinking strategies and teachers examination proposals in the classroom, which was carried out during the period 2001-2003 at Universidad Nacional del Comahue. The theoretical framework includes psychoanalysis and genetic psychology, since both trends allow for the study of the psychic singularity in its double dimension: cognitive and symbolic. The concept of strategy of thinking applied in order to carry out the research is the one developed by Narciso Benbenaste (1995). The qualitative methodology used included observations of the group-class and clinical interviews to the sample students following a clinico-critical approach. Students from a state school in Viedma, Río Negro, were selected for the empirical part of the research. The aim of this work was to identify the operative and symbolic mechanisms used by students of 3rd year EGB (primary school) to solve the situations presented in tests, especially in the areas of Language and Maths. Problem solving strategies have been identified, and it has been proved that students can solve a situation easily, in most cases with a low anxiety level, if it is not very different from the ones done previously in class. In several tests, students production answered what was asked by the teacher, in others they could establish more relations than those expressed in writing, such relations resulted from background knowledge or subjective appreciation. Exam situations are mainly regarded as stressful, very often determining students strategies to solve problems.